Evaluation of an Online Reading Programme to Improve Pupils' Reading Skills in Primary Schools: Outcomes from Two Implementation Studies. (1st November 2016) - Watkins, Richard; Hulson-Jones, Amy; Tyler, Emily; Beverley, Michael; Carl Hughes, J.; Hastings, Richard
Headsprout Early Reading (HER) is an online reading programme designed to teach pupils early reading skills. It uses adaptive technology to deliver systematic, synthetic phonics instruction, and is an effective supplementary teaching aid for beginning readers in mainstream and special schools (aged 4–7 years). In the current study, an evaluation of HER was conducted with two mainstream primary schools in north Wales. The primary aim was to investigate whether pupils receiving HER would improve early reading skills (i.e.catch-up) in School A compared to a control group in the same school. The secondary aim was to describe the use of HER without implementation support (School A) and with support (School B) following initial training of teaching assistants, and to present evidence about the reading outcomes for the pupils in the two schools. We report findings from twenty-nine year 2 pupils (6–7 years) in School A and fourteen year 2–6 pupils (6–11 years) in School B. Analysis of pre- and post-test standardised reading scores indicate statistically significant improvements in reading comprehension scores for HER pupils within School A compared to pupils not receiving intervention. There are also statistically significant improvements in pupils' DIBELS (correct words) sub-test measures in favour of the school receiving the implementation support (School B) compared to the school not receiving implementation support (School A). These results support previously reported findings that HER is an effective supplementary reading programme for struggling readers. It also indicates that schools can deliver HER more effectively with additional implementation support.